Islamist terrorism in Europe: a history - Nesser, Petter (Hurst & Company, 2018)
The 2012 Toulouse and Montauban shootings and the grisly murder of Lee Rigby in Woolwich in 2013 are stark reminders of the terrorist threat posed by militant Islamist extremism in Europe. While the death of Osama bin Laden and the advent of the 'Arab Spring' fed expectations that international jihadism was a spent force, Europe has faced an increase in terrorist plots over the past few years. In addition, there are growing security concerns over the fallout of the Syrian conflict, and its sizeable contingents of battle-hardened European fighters. This book provides a comprehensive account of the rise of jihadist militancy in Europe and offers a detailed background for understanding the current and future threat. Based on a wide range of new primary sources, it traces the phenomenon back to the late 1980s, and the formation of jihadist support networks in Europe in the early 1990s. Combining analytical rigour with empirical richness, the book offers a comprehensive account of patterns of terrorist cell formation and plots between 1995 and 2012.0In contrast to existing research which has emphasised social explanations, failed immigration and homegrown radicalism, this book highlights the entrepreneurial role of former Arab-Afghan veterans and their associated organisations and ideological agendas